ANALISIS STRATEGI PEMASARAN PINANG KERING PADA PEDAGANG DI KECAMATAN KUALA BETARA KABUPATEN TANJUNG JABUNG BARAT - Sigit Setia Darmadi; Ambok Pangiuk; Angger Hidayat (Nusantara Hasana Journal, 2026)
This study aims to analyze the marketing strategies of dried areca nut (pinang kering) implemented by traders in Kuala Betara District, Tanjung Jabung Barat Regency. Areca nut is one of the plantation commodities with high economic value and great potential to increase community income and national foreign exchange through exports. However, in this region, the marketing of dried areca nut still faces various challenges, such as suboptimal product quality, limited transportation access, and predominantly traditional marketing strategies. This research employs a qualitative approach, utilizing data collection techniques such as observation, indepth interviews, and documentation. The informants in this study are dried areca nut traders operating in the area. Data analysis was carried out through data reduction, data display, and conclusion drawing, with triangulation used to ensure data validity. The findings indicate that traders' marketing strategies include direct selling to middlemen, word-of-mouth promotion, and maintaining product quality to ensure customer loyalty. The study suggests the need for diversification of marketing channels through digital media, strengthening cooperatives or business groups, and improving product quality through training and processing facilities. With a more modern and integrated strategy, the marketing of dried areca nut from Kuala Betara District has the potential to expand to national and international markets.